2008
DOI: 10.1254/jphs.08244fp
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid Receptor Forms a Functional Heterodimer With Cannabinoid CB1 Receptor: Electrophysiological and FRET Assay Analysis

Abstract: Abstract. Interactions between μ-opioid receptor (μOR) and cannabinoid CB 1 receptor (CB 1 R) were examined by morphological and electrophysiological methods. In baby hamster kidney (BHK) cells coexpressing μOR fused to the yellow fluorescent protein Venus and CB 1 R fused to the cyan fluorescent protein Cerulean, both colors were detected on the cell surface; and fluorescence resonance energy transfer (FRET) analysis revealed that μOR and CB 1 R formed a heterodimer. Coimmunoprecipitation and Western blotting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 28 publications
3
89
0
2
Order By: Relevance
“…Because of these and other difficulties, the data obtained with western blotting cannot be accepted as conclusive evidence for CB 1 R homodimerization, and data obtained with other methods are necessary to verify these findings. Using resonance energy transfer methods, heterodimerization of CB 1 R with D 2 and A 2A receptors (Carriba et al 2008), opiate receptors (Rios et al 2006) has been observed in transfected cells, and the functional role of these heterodimerizations has also been suggested (Hojo et al 2008, Marcellino et al 2008. Although bioluminescence resonance energy transfer (BRET) has also been widely used in dimerization studies, it needs careful experimental design and appropriate controls to conclude on specific interaction between two receptors (Marullo & Bouvier 2007).…”
Section: Modulation Of Ion Channelsmentioning
confidence: 99%
“…Because of these and other difficulties, the data obtained with western blotting cannot be accepted as conclusive evidence for CB 1 R homodimerization, and data obtained with other methods are necessary to verify these findings. Using resonance energy transfer methods, heterodimerization of CB 1 R with D 2 and A 2A receptors (Carriba et al 2008), opiate receptors (Rios et al 2006) has been observed in transfected cells, and the functional role of these heterodimerizations has also been suggested (Hojo et al 2008, Marcellino et al 2008. Although bioluminescence resonance energy transfer (BRET) has also been widely used in dimerization studies, it needs careful experimental design and appropriate controls to conclude on specific interaction between two receptors (Marullo & Bouvier 2007).…”
Section: Modulation Of Ion Channelsmentioning
confidence: 99%
“…μ-Opioid and cannabinoid receptors are co-distributed in the area of the dorsal horn of the spinal cord and areas of the brain that control antinociceptive effects, such as the periaqueductal gray, raphe nuclei, and central medial thalamic nuclei (25). Biological and molecular biological findings suggest that cannabinoid receptors form heterodimers with μ-opioid receptors (26). Several behavioral effects that are induced by cannabinoid receptor agonists have been shown to at least partially depend on the activation of endogenous opioid systems, indicating that there is cross-talk between endogenous cannabinoid and opioid systems (27); the opioid receptor antagonist naloxone could attenuate the discriminative stimulus effects of THC (28), suggesting that the endogenous opioid system is involved in the discriminative stimulus effects of THC.…”
Section: Discriminative Stimulus Effects Of Cannabinoidsmentioning
confidence: 99%
“…Also, splice variants of MOR have been reported for rodents and humans (16), and can result in isoforms with varying trafficking and signaling properties (17). Also, the MOR has been shown to oligomerize with other opioid receptors (18,19), and with receptors in other classes (20,21), which can significantly alter receptor function (10,22). Sequencing of OPRM1 has identified a number of nonsynonymous SNPs that alter the resulting protein.…”
mentioning
confidence: 99%